PROBLEM-SOLVING ASSESSMENT IN MODIFYING TASKS - Subekti, Puji (Universitas Negeri Malang, 2019)
An assessment has many benefits, especially in efforts to modify tasks. Often the teacher overrides the process of assessing students in problem-solving. Teachers use easy methods to teach. This causes students only to be able to practice questions and solutions conceptually and cannot develop their creativity in problem-solving. In this study aims to assess prospective teachers to accomplish problem-solving so that they can be creative in modifying tasks for students. The main aspect of this study is to provide an assessment of the problem-solving ability so that prospective teachers can change the new assignment. Students were practicing using an approach to a multi-dimensional perspective SPUR. Can make students excited and try to be creative in modifying the task.